A Comprehensive Approach to University Wellness Emphasizing Million Hearts® Demonstrates Improvement in Population Cardiovascular Risk - Melnyk, Bernadette Mazurek; Gascon, Gregg M.; Amaya, Megan; Mehta, Laxmi S. (Building Healthy Academic Communities Journal, 2018)
Purpose: This study evaluated changes in university faculty and staff cardiovascular population risk over a three-year period after the implementation of the Million Hearts®' initiative, which targets the ABCS for cardiac care (i.e., Appropriate aspirin therapy, Blood pressure control, Cholesterol management, and Smoking cessation), with an additional S for Stress reduction. Methods: Using a longitudinal descriptive analysis of population cardiovascular health from 2012 to 2015, the Framingham Risk criteria for over 28,000 continuously-enrolled university faculty and staff were examined in a quality improvement initiative following the implementation of the Million Hearts® national initiative. Launched in 2011 by the Centers for Disease Control and Prevention and the Center for Medicaid Services within the Department of Health and Human Services, the initiative targets modifiable risk factors to prevent one million heart attacks and strokes by 2022. Results: Faculty and staff with low-risk Framingham scores increased from 7.8 % to 14.1 % from 2012 to 2015. Conclusion: Although this study was not a randomized controlled trial, findings support a comprehensive integrated approach to population health and wellness, emphasizing the ABCS of Million Hearts® with an added S for Stress reduction, can improve cardiovascular disease risk.